Evaluation of performance of Indonesian Sepsis National Guidelines (PNPK) 2021 in diagnosing pediatric bacterial sepsis - asiyani, Lilis siti; Rusmawatiningtyas, Desy; Indrawanti, Ratni Indrawanti; Arguni, Eggi Arguni; Wibowo, Tunjung Wibowo; Nurnaningsih, Nurnaningsih Nurnaningsih (Paediatrica Indonesiana, 2024)
Background Sepsis remains one of the causes of child morbidity and mortality worldwide. The reference standard diagnosis of sepsis is blood culture, but its false negative is relatively high. Therefore, a validated triage tool is needed for rapid diagnosis. In Indonesia, diagnosis and management of pediatric sepsis are based on Indonesian Sepsis National Guidelines 2021. Objective To evaluate the performance of Indonesian Sepsis National Guidelines 2021 in diagnosing pediatric bacterial sepsis in PICU. Methods This cross-sectional study was conducted in the PICU unit of Dr. Sardjito Hospital, Yogyakarta, using subject’s the medical records. All patients with suspected bacterial infection who were admitted to the PICU, had complete evaluation of PELOD-2 score, and the blood culture results were included in this study. Sepsis was assessed with Indonesian Sepsis National Guidelines 2021. Performance analysis of the guidelines was conducted with SPSS version 25, by assessing sensitivity, specificity, accuracy, positive predictive value, negative predictive value, and likelihood ratio. Results Two hundred subjects were enrolled in this study, of whom 52.5% were males. Most subjects aged under one year (40.5%), and the most common infection was respiratory system (49%). A total of 63.5% were referral cases, with the length of stay in the previous hospital more than 48 hours (69.7%). There were 77% of subjects had antibiotics treatment at the previous hospital. As for outcomes, 63.5% survived and 36.5% died. The positivity rate of blood culture in this study was 19%. Performance evaluation of Sepsis Indonesian Sepsis National Guidelines 2021 revealed sensitivity 28.95%, specificity 87.65%, accuracy 76.5%, positive predictive value 35.48%, negative predictive value 84.02%, positive likelihood ratio 2.34 (95%CI 1.28 to 4.32) and negative likelihood ratio 0.81 (95%CI 0.7 to 0.94). Conclusion Indonesian Sepsis National Guidelines 2021 (PNPK Sepsis 2021) has low sensitivity and high specificity in diagnosing bacterial sepsis.